The impact of dictogloss and blogging on EFL students’ writing skills in an Indonesian tertiary vocational college - Sri Hardiningsih; Elizabeth Anggraeni Amalo (JOALL (Journal of Applied Linguistics and Literature), 2023)
The purpose of this study is to assess students' writing abilities using dictogloss and blogging. It involved 24 students from vocational colleges and incorporated five audio scripts from Hughes and Naunton's "Students Book of Business Results (Intermediate)" (2008). It employed a mixed method in the form of a quasi-experimental. The data was acquired using questionnaires and interviews. The students were divided into two groups: half were assigned to the control group, while the other half were assigned to the experimental group, which received training while the control group did not. The experimental group achieved a score of 59, whereas the control group achieved an average score of 41. Future research should look in depth at how creatively tertiary vocational college students think, especially through listening activities.